Analisis Pengaruh Corporate Social Responsibility Terhadap Kinerja Finansial Perusahaan dengan Culture dan Corporate Governance sebagai Variabel Pemoderasi: Studi Empiris Pada Perusahaan Listing di Bursa Efek Indonesia - Indah Novita Sari; Lulus Kurniasih (Conference In Business, Accounting, And Management (CBAM), 2012)
The purpose of this study is to examine the effect of culture and corporate governance on its corporate social responsibility disclosures. For further, this study aims to obtain the empirical evidence about the effect of corporate social responsibility on its corporate financial performance with culture and corporate governance as moderating variables.Corporate governance are identified as the proportion of the audit committee, the number of commissary board meetings, and the proportion of managerial ownership. The culture are identified as the proportion of Indonesian board of directors, Indonesian board of commissioners, and foreign ownership. Corporate social responsibility disclosures are measured by using corporate social responsibility index. Then, the corporate financial performance are measured by Return on Assets (ROA). This study includes firm size and leverage as control variables. Under purposive sampling method, 153 companies that listed in Indonesia Stock Exchange are selected. This study employed a data testing technique: classical assumption, descriptive statistic, and hypothesis test using ordinary least square regression. Analysis of statistical result that foreign ownership is a significant predictor to corporate social disclosure. The firm size as control variable also affects corporate social responsibility disclosure. In addition, culture and corporate governance have no signifficant effect in mediating the relationship between corporate social responsibility and corporate financial performance.Keywords : corporate social responsibility, culture, corporate governance, corporate financial performance